Answer: A
Step-by-step explanation:
Answer:
n = 0, n =2
Step-by-step explanation:
Given
(n + 1) + 3(n - 1) = 2(n - 1)(n + 1) ← distribute parenthesis on both sides
n + 1 + 3n - 3 = 2(n² - 1), that is
4n - 2 = 2n² - 2 ( subtract 4n - 2 from both sides )
0 = 2n² - 4n ← factor out 2n from each term )
0 = 2n(n - 2)
Equate each factor to zero and solve for n
2n = 0 ⇒ n = 0
n - 2 = 0 ⇒ n = 2
Answer:
Step-by-step explanation: 252 apex
There are 128 fluid oz in 1 gallon
10*128=1280
so they are both the same
10 gallons=1280 fluid oz